MERETAS PENDIDIKAN TERINTEGRATIF PADA MATA KULIAH PENDIDIKAN KEWARGANEGARAAN DI PERGURUAN TINGGI KEAGAMAAN ISLAM NEGERI: Transformasi Ideologi Pancasila dan Deradikalisasi - Arief Adi Purwoko (IAIN Pontianak, 2020)
Ideology is an important part of human life, both as ideals and the system of thinking. Nevertheless not many realize, that ideology is a construction, either consciously or naturally formed. This article is a literature study, in an effort to uncover and illustrate contemplatively the development of education of ideology, especially by placing civic education at Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) as a filter of the radicalisation. The strategy offered is the adoption of integrated curriculum to raise students’ conscientization. The article discusses the transformation of Pancasila ideology through: i) urgency of civic education in PTKIN; II) The role of PTKIN to convey Pancasila as national ideology; and (iii) an integrated curriculum model in civic education as an ideological transformation effort. The discussion will begin from the role of PTKIN as a government representative in implementing education, which is to educate citizens as well as assert Pancasila as a nation's ideology. PTKIN must be able to translate the universal values of Islam and Pancasila, without any conflict. At the same time, the citizenship education in it does not have to be interpreted as a doctrinal space, but rather a dialogical space between the universal values of which — manifested in both the theory and the legal evidence — in various events. It will also comparatively describe that “stick and carrot model” would rather keep away from education goals, only create fear, and not differ from the pattern of a radicalism. In conclusion, the integrated curriculum involves the creation of products from various branches of science, multidisciplinary, especially from the scientific work that has been produced by PTKIN, as well as studies adopted from Islamic Studies. By adopting the integrated curriculum, hopefully, will be formed a holistic understanding of students, so that with the conscientization, independently will be able to analyse the threat of radicalism for the existence of the Republic of Indonesia.